Numerical models performance to predict drying liquid water in porous building materials: Comparison of experimental and simulated drying water content profiles. Issue 1 (1st January 2017) - Guimarães, A.S.; Ribeiro, I.M.; de Freitas, V.P.
Abstract: A practical way to evaluate drying in porous building materials is through environmental conditioning drying curve where drying is influenced by external factors such as environmental conditions and by the material properties. However, attaining drying curves can be an extremely slow process, which can be unsuited with the schedule and the available resources. This work describes the drying process in porous building materials using the simulation tool "TRHumidade" for the determination of water content profiles inside those materials and comparing with the well-known simulation tool "WUFI Pro" and experimental results obtained by gamma ray. One of the main goals is to validate the use of TRHumidade and evaluate the better tool (TRHumidade vs. WUFI Pro) to describe liquid phase drying processes, to evaluate if the water content potential describes better the drying phenomenon. The numerical results obtained with TRHumidade and WUFI simulation tools are similar to the experimental ones obtained by gamma ray. In the surfaces, TRHumidade reveals better results than WUFI Pro. Those results means that the TRHumidade can easily be used to study the drying process of the porous building materials.